Pemanfaatan Desain Tata Ruang pada Ruang Baca Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Sijunjung - Cut Afrina; Riawan Aristya Cahyani; Saifuddin Rasyid; Silvi Gusti Wahyuni; Zurriyati Husni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The public library is the closest institution to the community, with a library, it is easy for the community to find learning resources that suit their needs. This research aims to determine the utilization of spatial design in reading room study to determine the use of spatial design in the reading room at the library service and the general archives of the sijunjung area and to find out which reading room complies with existing library guidelines. The method used in this study is qualitative. The data collected in this study by conducting observations, interviews, and literature studies that are directly related to the research. From the result of this study, it can be concluded that the layout design of the library service and the general archives of the sijunjung area is quite good and the lighting and color of the room look elegant so that when the user enters the room it makes the mind of the user calm and open